2023
DOI: 10.1002/cam4.5200
|View full text |Cite
|
Sign up to set email alerts
|

The link between psychological distress and survival in solid tumor patients: A systematic review

Abstract: Purpose Research has demonstrated that solid tumor patients experience high levels of psychological distress at the time of diagnosis. While distress has been associated with many adverse clinical outcomes, little is known about how this symptom may influence the disease trajectory for cancer patients, affecting outcomes such as progression, recurrence, and survival. The purpose of this systematic review was to explore the literature linking distress with survival in solid tumor patients, which ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Our results show not only that the well-being of these individuals is compromised, but also, given the existing literature, that they are exposed to cellular changes that facilitate the proliferation of cancer cells and thus influence the prevalence of the disease. Furthermore, these stress levels influence the course of the disease, leading to physical deterioration, and are associated with lower survival rates and a poorer response to treatment [ 19 , 20 , 21 , 22 ]. It should be noted that in our study, patients who perceived high and very high levels of stress were more likely to develop paralytic ileus ( p = 0.002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results show not only that the well-being of these individuals is compromised, but also, given the existing literature, that they are exposed to cellular changes that facilitate the proliferation of cancer cells and thus influence the prevalence of the disease. Furthermore, these stress levels influence the course of the disease, leading to physical deterioration, and are associated with lower survival rates and a poorer response to treatment [ 19 , 20 , 21 , 22 ]. It should be noted that in our study, patients who perceived high and very high levels of stress were more likely to develop paralytic ileus ( p = 0.002).…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that active coping styles predominate. These contribute to a greater adjustment to the illness and lower stress levels in the patients, due to the beneficial effects of active coping styles on stress [ 10 , 46 ] and hence they improve their psychological situation, the non-proliferation of cancer cells, and enable better management of the disease and its circumstances [ 19 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pooled data from 16 prospective studies, reporting 4353 cancer related deaths, revealed that higher levels of distress were associated with a 32% greater mortality risk [70]. A 2023 systematic review reported that presence of psychological distress was predictive of reduced survival across 11 of the 13 reviewed studies [71].…”
Section: Psychological Healthmentioning
confidence: 99%
“…In our recent study, 29 patients with the highest occurrence rates for shortness of breath reported higher levels of global, cancer‐related, and cumulative life stress. Given that a cancer diagnosis and its associated treatments are extremely stressful experiences, 30 , 31 and albeit limited information on positive associations between the occurrence and severity of shortness of breath and stress, an examination of its associations with both severity and distress is warranted. Equally important, evidence suggests that resilience facilitates a positive cognitive appraisal of perceived stress.…”
Section: Introductionmentioning
confidence: 99%